Multiple submission of the same manuscript to scientific journals for publication: ignorance or deliberate act ?: ethical considerations and editorial implications (Publicaciones en Ciencias y Tecnología, 2021)
The urgency or need for acceptance of the publication of a scientific article may lead some authors to make the decision, naive or deliberate, to send the same manuscript to more than one scientific journal, which entails ethical considerations and consequences for both the journals involved as well as the authors. This Editorial presents a brief reflection on the importance of safeguarding the unpublished character of the submitted works, maintaining the commitment not to send it simultaneously to other journals, as well as not having previously published it.
Keywords: Editorial; edundant submit